Postoperative Refraction in the Second Eye Having Cataract Surgery. (10th December 2011) - Leffler, Christopher T.; Wilkes, Martin; Reeves, Juliana; Mahmood, Muneera A.
Abstract : Introduction . Previous cataract surgery studies assumed that first-eye predicted and observed postoperative refractions are equally important for predicting second-eye postoperative refraction. Methods . In a retrospective analysis of 173 patients having bilateral sequential phacoemulsification, multivariable linear regression was used to predict the second-eye postoperative refraction based on refractions predicted by the SRK-T formula for both eyes, the first-eye postoperative refraction, and the difference in IOL selected between eyes. Results . The first-eye observed postoperative refraction was an independent predictor of the second eye postoperative refraction (P < 0.001 ) and was weighted more heavily than the first-eye predicted refraction. Compared with the SRK-T formula, this model reduced the root-mean-squared (RMS) error of the predicted refraction by 11.3%. Conclusions . The first-eye postoperative refraction is an independent predictor of the second-eye postoperative refraction. The first-eye predicted refraction is less important. These findings may be due to interocular symmetry.